Ethics in professional practices in Nigeria (Lagos, Nigeria : Association of professional bodies in Nigeria, 2002)
''Ethics in Professional in Nigeria'' is an edited compilation of papers presented at a two-day seminar organized by the association of Professional Bodies in Nigeria(APBN) at Lagos on the 19th & 20th October- 1999. The seminar was aimed at focusing desirable and important attention on the subject of ethics of the various member bodies of APBN.